God's Holy People : a Theme in Biblical Theology - Wells, Jo Bailey (Journal for the study of the Old Testament. Supplement series ;, 2000)
God calls his people to be holy. What does this mean? Holiness means belonging to God and being stamped with his character. This belonging is expressed for ancient Israel in the story of the foundational events on Mount Sinai. The idea is then developed, refined and transformed through the establishment of the priesthood, the gift of the Law, the challenge of the prophets and, in the New Testament, through the life of Christ. This book sets out these perspectives alongside each other, and considers their interplay within the canon of scripture as a whole.